Supplemental report concerning the use of Stilbestrol - Bell, T.D.; Smith, W.H.; Erhart, A.B. (Kansas Agricultural Experiment Station, 2012)
Since the preparation of the original report on the lamb feeding studies at the Garden City Station, additional information has been obtained concerning the effect of stilbestrol upon the reproductive organs of wether lambs which may result in serious malfunction of the excretory system and possible death of the treated animals.
Keywords: Sheep; Stilbestrol; Gain; Reproductive organs